2019
DOI: 10.1177/1524838019870917
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Cycles of Maltreatment: A Scoping Review of Psychosocial Risk and Protective Factors

Abstract: Child maltreatment tends to show intergenerational continuity. However, a significant proportion of maltreated parents break these cycles. Since several studies have investigated risk and protective factors associated with the intergenerational continuity of child maltreatment over the past decades, and no systematic review of the literature is available, this scoping review aimed to summarize studies documenting associated psychosocial risk and protective factors. A secondary objective was to document the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(100 citation statements)
references
References 75 publications
6
91
0
3
Order By: Relevance
“…), (Lacey et al, 2020). This variable consistently emerges as a probable mechanism involved in intergenerational transmission (Berzenski et al, 2014;Langevin et al, 2019). Household mental illness has been linked to a higher risk of internalizing problems, such as depression and anxiety (Bevilacqua et al, 2021;Muniz et al, 2019), as well as to a higher risk of externalizing problems (aggression, conduct problems, and criminal activity in children), (Anderson & Hammen, 1993).…”
Section: Intergenerational Transmission and Household Dysfunctionsmentioning
confidence: 99%
See 3 more Smart Citations
“…), (Lacey et al, 2020). This variable consistently emerges as a probable mechanism involved in intergenerational transmission (Berzenski et al, 2014;Langevin et al, 2019). Household mental illness has been linked to a higher risk of internalizing problems, such as depression and anxiety (Bevilacqua et al, 2021;Muniz et al, 2019), as well as to a higher risk of externalizing problems (aggression, conduct problems, and criminal activity in children), (Anderson & Hammen, 1993).…”
Section: Intergenerational Transmission and Household Dysfunctionsmentioning
confidence: 99%
“…In contrast to other family dysfunctions, studies have mainly yielded mixed results regarding household substance abuse and intergenerational transmission (Langevin et al, 2019). The studies showing a positive link between the two variables showed that children whose parents consume illegal substances were more likely to also use drugs (Augustyn et al, 2020;Kerr et al, 2020).…”
Section: Intergenerational Transmission and Household Dysfunctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results show the protective role of social support on subsequent violence, depending on the kind of violence history and timing (Tracy et al, 2018 ). Furthermore, higher socioeconomic status, positive relationships with the offspring, higher levels of satisfaction with parenthood, and functional interpersonal relationships in adulthood were found to mitigate this intergenerational transmission (McClellan and Killeen, 2000 ; Tracy et al, 2018 ; Langevin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%